Hydro-cultural growing of cut flower in greenhouse - Lévai, Péter; Turiné Farkas, Zsuzsa (Acta Agraria Debreceniensis, 2007)
The closed system hydro-cultural growing is environmentfriendly,  the chemical fertilizer used for nourishing material supply does not contaminate the soil water and it is possible to eliminate the chemical materials accumulating during the disinfection of the soil getting into the environment. It can be mechanized and regulated well so the optimum growing conditions can be fixed for the plant and as a consequence higher yield can be reached both for the carnation and for Zantedeschia and for Rosa. Growing method with saving both the nourishing material and the water. Taking all the above into consideration timing is easier and better, it can be programmed better than the traditional chemo-cultural growing.